2016
DOI: 10.1108/jbim-04-2014-0071
|View full text |Cite
|
Sign up to set email alerts
|

Types of embedded ties in buyer-supplier relationships and their combined effects on innovation performance

Abstract: Purpose of the Paper -This research analyzes the impact of three types of embedded ties, namely, specialized complementary resources, idiosyncratic investments, and knowledge sharing, on the innovation capacity of the firms. We also study the particularities of the Machine-Tool industry. Theoretical background -Our evaluation of the embedded buyer-supplier ties is based on the potential sources of relational rents proposed by Dyer and Sing (1998). We also draw on Uzzi and Lancaster (2003), Noordhoff et al. (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 81 publications
(163 reference statements)
2
38
0
Order By: Relevance
“…The process consists of different phases such as the strategy of new products/services, screening, idea generation, concept testing, NPD business analysis, testing development, a thorough marketing mix and the commercializing of the final product to the public or marketplace [67]. Past literature has indicated that researchers have discussed product innovation widely regarding the concept of new product development [66,[69][70][71][72]. Previous studies identified that various scholars published several dozen articles in innovation and marketing literature that focused on the product launch issues faced by business firms [73][74][75][76].…”
Section: New Product Developmentmentioning
confidence: 99%
“…The process consists of different phases such as the strategy of new products/services, screening, idea generation, concept testing, NPD business analysis, testing development, a thorough marketing mix and the commercializing of the final product to the public or marketplace [67]. Past literature has indicated that researchers have discussed product innovation widely regarding the concept of new product development [66,[69][70][71][72]. Previous studies identified that various scholars published several dozen articles in innovation and marketing literature that focused on the product launch issues faced by business firms [73][74][75][76].…”
Section: New Product Developmentmentioning
confidence: 99%
“…Given this cooperative relationship, innovation processes will occur more effectively [39]. Another research by Charterina et al [15] says that innovation can be enhanced through good partnership relationships between buyer and supplier companies. Intense communication and knowledge sharing between buyers and suppliers will increase the probability of finding a novelty, a key to the innovation process.…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…Good relationships between buyer and supplier companies also enable the innovation process. Intense communication and knowledge sharing between buyers and suppliers increase the probability of finding a novelty, a key environment to the innovation process [15]. As in reference [16] states that there are two main points in the relationship between buyers and suppliers that lead to innovation, first: internal relationships including commitment, trust, mutual adoption of knowledge between organizations, information systems, and second: external relationships including demand stability, and intercompany network connection.…”
Section: Introductionmentioning
confidence: 99%
“…Past research analyzed the effects such as industry structure and growth level (Chen, 2009) or uncertainty and instability in the industry (Padula andDagnino 2007, Ritala 2012). Some peculiarities of the MT industry markedly illustrate these conditioning effects: First, customers are the main source of innovation in the MT industry (Carlsson, 1995;Charterina et al 2016Charterina et al , 2017Chen, 2009;Lissoni, 2001, Lissoni andPagani, 2003;Mazzoleni, 1997Mazzoleni, , 1999Otero, 2010). A growing problem for many SMEs in the European MT industry is that an increasing share of the customers that purchase MTs is in far, distant markets.…”
Section: 2-external Drivers Pushing Towards Coopetition In the Mt mentioning
confidence: 99%